ATOMISTIC SIMULATION OF THE STRUCTURE AND SEGREGATION TO THE (0001) AND (0112) SURFACES OF FE2O3 - Cooke D.J.; Redfern S.E.; Parker S.C. (My University, 2004)
The segregation of ten isovalent impurities (Al3+ Cr3+, Eu3+, Gd3+, Ho3+, La3+, Lu3+, Nd3+, Tb3+, Y3+) to the and the (0001) surfaces of haematite (α-Fe2O3) have been studied using atomistic simulation where the forces between the atoms are modelled using the Born model of solids. Segregation is found to be energetically favoured in virtually every case. The results for the surface show that the most favourable impurity surface concentration is 33.33%. The (0001) surface has two possible terminations, one terminated by iron atoms and the other by oxygen. No minimum is calculated for the Fe termination of the (0001) surface at low temperatures, but when the effect of raising the temperature is considered, an energy minimum is found, also at 33.33% impurity coverage. In contrast, the O terminated (0001) surface has a minimum in the segregation energy for between 16.67 and 33.33% depending on the cation being considered.
Keywords: Surface of haematite; Low index surfaces; Segregation; Atomistic simulation